What does it cost to deliver antenatal care in Papua New Guinea? Results from a health system costing and budget impact analysis using cross-sectional data - William Pomat; Rebecca Guy; Handan Wand; John M Kaldor; Nicola Low; Suzanne M Garland; Christopher Morgan; Angela Kelly-Hanku; Sepehr Tabrizi; Lisa Vallely; Andrew Vallely; Virginia Wiseman; et al. (BMJ Open)
Objective In Papua New Guinea (PNG), antenatal clinic attendance averaged 50% for one or more visits, and 30% for four visits in the last decade. In 2016, the WHO revised its focused antenatal care (ANC) model recommending eight rather than four visits. If implemented, this new model would require additional resources. This study estimated provider costs of ANC in PNG, including the expected cost of scaling up to universal ANC coverage as well as recommending eight visits.Design and setting Cross-sectional estimation of ANC costs collected from nine health facilities, which were part of a cluster randomised trial. Costs were estimated using both top-down and bottom-up approaches. The cost of the first and follow-up visits were estimated per woman, at the health facility level. Health system and scale-up costs of four visits were calculated by multiplying the aggregate cost of four visits by ANC utilisation rates. A budget impact analysis estimated the expected costs of delivering eight visits over 5 years. Univariate sensitivity analysis was conducted. Discounted costs are reported in local currency and 2019 international dollars using purchasing power parity data.Results The average cost of the first and follow-up visits were $17.66–$30.58 (K42.94–K74.34) in Madang and $11.26–$35.61 (K27.37–K86.56) in East New Britain. Four visits per woman cost $70.65–$122.33 (K171.76–K297.36) in Madang and $45.02–$142.45 (K109.50–K346.4) in East New Britain; and salaries represented the largest share of costs. The annual health system cost was $6.9 million (K16.9 million), the expected cost of scaling up to the universal coverage of four visits was $22.7 million (K55.2 million), and $45.4 million (K110.3 million) over 5 years for eight visits.Conclusion Costs varied with the number of clinicians, infrastructure and ANC coverage, suggesting scaling up requires increasing the financial investment in ANC services. These results provide a template to strengthen health systems by improving the quality of care.